Overexpression of fibroblast growth factor receptor 2 in bone marrow mesenchymal stem cells enhances osteogenesis and promotes critical cranial bone defect regeneration - Zhou, Yiwen; Zhu, Peixiang; Shen, Siyu; Wang, Yanyi; Li, Baochao; Guo, Baosheng; Li, Huang (Frontiers in Cell and Developmental Biology, 2023)
Background: Reconstruction of cranial bone defects is one of the most challenging problems in reconstructive surgery, and several biological tissue engineering methods have been used to promote bone repair, such as genetic engineering of bone marrow mesenchymal stem cells (BMSCs). Fibroblast growth factor receptor 2 (Fgfr2) is an important regulator of bone construction and can be used as a potential gene editing site. However, its role in the osteogenesis process of BMSCs remains unclear. This article clarifies the function of Fgfr2 in BMSCs and explores the role of Fgfr2-overexpressed BMSCs carried by light-induced porous hydrogel (GelMA) in the repair of cranial bone defects. Methods: Lenti-virus was used to overexpress Fgfr2 in BMSCs, and cell counting kit-8, transwell, and flow cytometry assays were conducted to investigate the proliferation, migration, and characteristics. After 0, 3, 7, and 10 days of osteogenic or chondrogenic induction, the changes in osteogenic and chondrogenic ability were detected by real-time PCR, western blot, alkaline phosphatase staining, alizarin Red staining, and Alcian blue staining. To investigate the viability of BMSCs carried by GelMA, calcein and propyl iodide staining were carried out as well. Finally, a critical cranial bone defect model was established in 6-week-old male mice and micro-computerized tomography, masson staining, and immunohistochemistry of OCN were conducted to test the bone regeneration properties of implanting Fgfr2-overexpressed BMSCs with GelMA in cranial bone defects over 6 weeks. Results: Overexpression of Fgfr2 in BMSCs significantly promoted cell proliferation and migration and increased the percentage of CD200+CD105+ cells. After osteogenic and chondrogenic induction, Fgfr2 overexpression enhanced both osteogenic and chondrogenic ability. Furthermore, in cranial bone defect regeneration, BMSCs carried by light-induced GelMA showed favorable biocompatibility, and Fgfr2-overexpressed BMSCs induced superior cranial bone regeneration compared to a normal BMSCs group and an untreated blank group. Conclusions: In vitro, Fgfr2 enhanced the proliferation, migration, and stemness of BMSCs and promoted osteogenesis and chondrogenesis after parallel induction. In vivo, BMSCs with Fgfr2 overexpression carried by GelMA showed favorable performance in treating critical cranial bone defects. This study clarifies the multiple functions of Fgfr2 in BMSCs and provides a new method for future tissue engineering.